2001
DOI: 10.1108/13552550110396095
|View full text |Cite
|
Sign up to set email alerts
|

The sustainability of growth in small‐ and medium‐sized enterprises

Abstract: This paper explores the factors that determine the sustainability of growth in small‐ and medium‐sized enterprises (SMEs). Previous research has shown that SME growth may be the consequence of the strategic choices of entrepreneurs or the structural characteristics of the external environment. This research investigates the dynamic between these two “conflicting” explanations. Two in‐depth longitudinal case studies are presented of SMEs in the wholesale sector. For SME managers, this research suggests that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 28 publications
2
88
0
5
Order By: Relevance
“…According to Analou and Karami [3], developing a mission statement is considered to be a crucial factor in the formulation of sustainable business strategy in organizations. In the article by O'Gorman [4], the factors that determine the sustainability of growth in SMEs were explored and it was found that defining a strategic plan is an important element.…”
Section: Introductionmentioning
confidence: 99%
“…According to Analou and Karami [3], developing a mission statement is considered to be a crucial factor in the formulation of sustainable business strategy in organizations. In the article by O'Gorman [4], the factors that determine the sustainability of growth in SMEs were explored and it was found that defining a strategic plan is an important element.…”
Section: Introductionmentioning
confidence: 99%
“…Elle englobe également la théorie de l'écologie des populations (Hannan et Freeman, 1977) qui soutient que les conditions présentes dans l'environnement externe de la firme sont les principaux déterminants de la survie d'une entreprise. Remarquons toutefois que les seules dimensions exogènes sont insuffisantes pour comprendre la croissance des PME (O'Gorman, 2001). …”
Section: Les Facteurs Liés Au Secteurunclassified
“…Une entreprise exportatrice est, par exemple, plus susceptible de croître qu'une autre (O'Gorman, 2001 ;Wijewardena et Tibbits, 1999 ;Dobbs et Hamilton, 2007 ;Beck, Demirguc-Kunt et Maksimovic, 2005). Toutefois, l'internationalisation peut conduire l'entreprise à investir des marchés risqués et moins bien connus, et donc compromettre sa croissance.…”
Section: Les Facteurs Liés Aux Choix Stratégiquesunclassified
“…If instead of focusing on defining the characteristics/traits of the manager, one follows the idea of Wiklund (1998), focusing on what the managers actually do and how this work relates to growth, it seems a promising way to reach an understanding of the relation between top-managers' work and growth. This view also opens the possibility of joining the research tradition of traits with studies that have focused on the behaviour/roles of the entrepreneur/top-manager (for instance Choran 1969in Mintzberg 1973, Noel 1989, O'Gorman 2001, Florén and Tell 2004.…”
Section: Introductionmentioning
confidence: 99%